Kume tigra, a new genus and new species of carupine swimming crab (Crustacea: Brachyura: Portunidae) from Kume Island, Ryukyu Islands, Japan - Naruse, Tohru; Ng, Peter K. L. (Zootaxa, 2012)
A new genus and species of swimming crab of the family Portunidae Rafinesque, 1815, is described from Kume Island,Ryukyus, Japan. The new genus of the subfamily Carupinae Paul’son, 1875 is allied to the genera Pele Ng, 2011, andLibystes A. Milne-Edwards, 1867, but differs in the shapes of the carapace, thoracic sternum, third maxilliped, merus of the cheliped, fifth pereiopod, male abdomen and gonopods.